The Effect of the Most-Attractive-Distractor Location on Multiple-Choice Item Difficulty. Issue 4 (3rd August 2020) - Shin, Jinnie; Bulut, Okan; Gierl, Mark J.
Abstract: The arrangement of response options in multiple-choice (MC) items, especially the location of the most attractive distractor, is considered critical in constructing high-quality MC items. In the current study, a sample of 496 undergraduate students taking an educational assessment course was given three test forms consisting of the same items but the positions of the most attractive distractor varied across the forms. Using a multiple-indicators–multiple-causes (MIMIC) approach, the effects of the most attractive distractor's positions on item difficulty were investigated. The results indicated that the relative placement of the most attractive distractor and the distance between the most attractive distractor and the keyed option affected students' response behaviors. Moreover, low-achieving students were more susceptible to response-position changes than high-achieving students.